2022
DOI: 10.3390/molecules27051480
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition Analysis, Cytotoxic, Antimicrobial and Antioxidant Activities of Physalis angulata L.: A Comparative Study of Leaves and Fruit

Abstract: Physalis angulata L. belongs to the family Solanaceae and is distributed throughout the tropical and subtropical regions. Physalis angulata leaf and fruit extracts were assessed for in vitro anticancer, antioxidant activity, and total phenolic and flavonoid content. The GC-MS technique investigated the chemical composition and structure of bioactive chemicals reported in extracts. The anticancer activity results revealed a decrease in the percentage of anticancer cells’ viability in a concentration- and time-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
0
24
0
2
Order By: Relevance
“…Based on [25], extracts of plant compounds have MIC values ranging from 0.008 to 256 mg/ml, the research also revealed that ethanol extract had more potency than aqueous extract. Ciplukan ethanol extract has a MIC value of 10 mg/ml on E. coli and S. aureus bacteria as well as shown in the study of [4]. The 30 mins ultrasonic treatments are the best treatment to obtain antibacterial activity, the longer the sonication time, the temperature of the instrument also increases, which causes some heat-sensitive compounds to be damaged.…”
Section: Antibacterial Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…Based on [25], extracts of plant compounds have MIC values ranging from 0.008 to 256 mg/ml, the research also revealed that ethanol extract had more potency than aqueous extract. Ciplukan ethanol extract has a MIC value of 10 mg/ml on E. coli and S. aureus bacteria as well as shown in the study of [4]. The 30 mins ultrasonic treatments are the best treatment to obtain antibacterial activity, the longer the sonication time, the temperature of the instrument also increases, which causes some heat-sensitive compounds to be damaged.…”
Section: Antibacterial Activitymentioning
confidence: 94%
“…The study by [6] on ciplukan fruit showed that the total phenol obtained from ethanol and water extracts was 0.51 mg GAE/g and 0.46 mg GAE/g, respectively. Another study reported related to the total phenolic and flavonoid content of ciplukan using three different solvents (petroleum ether, ethyl acetate, and ethanol), the ciplukan extract using ethanol solvent had the highest content for total phenol and total flavonoid with values of 106.54 mg GAE/ g and 370.64 ± 4.33 mg QE/g, respectively [4]. In addition, study by [17] showed an increase in UAE temperature (20°C-60°C) directly proportional to an increase in total phenols and total flavonoids.…”
Section: Antioxidant Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, they reported that the fruit extract contained more flavonoid and phenol compounds than leaves. Hence, the bioactive compounds belonging to these phytochemicals effectively scavenge the H 2 O 2 [34]. Another species, Physalisperuviana, also reported possessing considerable H 2 O 2 scavenging activity.…”
Section: H 2 O 2 Scavenging Potentialmentioning
confidence: 96%
“…Recent phytochemical and pharmacological studies have confirmed that P. angulata is rich in vitamins, minerals, antioxidants, and many important pharmacologically active constituents, including antibacterial, anti-inflammatory, and anticancer ingredients [3][4][5][6]. In many countries, such as China, Indonesia, Peru, Mexico, and Brazil, P. angulata is often used to treat a variety of illnesses, including dermatitis, tracheitis, impaludism, rheumatism, hepatitis, and analogous conditions [7][8][9][10]. Recently, increasing attention has been paid to the phytochemical and pharmacological aspects of P. angulata, and a variety of bioactive steroids with antitumor activities, including physagulins (A−Q), physangulidines (A−C), withangulatins (A−I), physalins (B, D, F−H), and withaminimin, have been isolated from the species [4,5,11].…”
Section: Introductionmentioning
confidence: 99%